EDUKASI PENTINGNYA KESADARAN TERHADAP PENCEMARAN DI PESISIR PANTAI KAYUANGIN KECAMATAN SAMATURU KOLAKA - Syamsuri Syamsuri; Hasria Alang; Muh. Sri Yusal; Ibnu Mansyur Hamdani; Abdul Rahim; Mas'ati Mas'ati (Jurnal Abdimas Bina Bangsa, 2023)
Garbage is the most common thing that can be found in crowded places, such as beaches. The beach as a tourist attraction also contributes to the increasing amount of waste. Scattered garbage will affect the beauty, bota and human health. Changes in environmentally conscious attitudes can be done by providing education, outreach and direct examples. One way to make this happen is through the tridharma of community service from lecturers. The purpose of this activity is to provide education to the target audience about coastal pollution. The methods used in this education are lectures and discussions. The results of the service prove that there has been a change in the paradigm of partners before and after providing education. Public service target audiences no longer think that maintaining cleanliness is not their responsibility but a shared responsibility. The survey results after one month from the start of the service show that the beach tends to be cleaner than all. This means that service activities have added experience and an increase in the knowledge of participants/partners